Strategi Komunikasi Pemasaran Dinas Pariwisata Dalam Meningkatkan Kunjungan Wisata Di Danau Teloko Kayuagung - Fahmi Thohiri; Hamidah; Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is entitled Marketing Communication Strategy of the tourism office in increasing tourist visits at Lake Teloko Kayuagung. Tourism has many benefits for the community seen from several aspects, namely, economic, social, and cultural. In developing countries tourism is a mainstay of state income, such as Indonesia, Malaysia, Singapore and Thailand. Tourism development is closely related to the preservation of the nation's culture, by utilizing all the potential of natural beauty and natural wealth. Utilization here does not mean changing in total, but rather means managing, utilizing and preserving any existing potential, the potential can be a tourist attraction. The management and utilization of tourism potential owned by the region is also managed by each region. Likewise in Kayuagung which has a lot of potential and natural resources that can be developed as a tourist attraction and community recreation center. The purpose of this research is to find out the marketing communication strategy of the Tourism Office in Increasing Visits at Lake Teloko Kayuagung, and to find out what are the supporting and inhibiting factors for the Tourism Office in Increasing Tourist Visits at Lake Teloko. this research uses descriptive methods with a qualitative approach. This research uses the theory of the City as an Entertainment Machine proposed by Clark. The results of the study are Advertising, Public Relations, Publicity Sales Promotion, Personal Selling (Face-to-Face Sales) and the supporting factors of the OKI Regency Government Tourism Office in marketing, namely, Tourism Objects, Facilities and Infrastructure. As well as the inhibiting factors of the OKI Regency Government Tourism Office in marketing, namely, Regional Language, Human Resources.